PENERAPAN PELATIHAN TOEIC KEPADA GURU-GURU SDN PAGELARAN 04 BOGOR DALAM RANGKA PERSIAPAN SERTIFIKASI GURU - Kusumadewi, Hermariyanti; Candra, Eva Nurul (Universitas Esa Unggul, 2017)
AbstractTOEIC or the Test Of English for International Communication is the standard test used to measure the English language proficiency of non-English speakers in the English language daily in the workplace. Â Teacher certification is an absolute must-have for all teachers in Indonesia. Not infrequently the teachers are experiencing difficulties in working on the problems tested in the certification of teachers, because some of the problems presented in the form of English. Many things can support a teacher pass the certification. Not only about the filing associated with the teachers working lives in school, but passing a written test is also very influential in teacher certification. Sometimes elementary teachers do not pass the written test because they are less familiar with English problems. Even English teachers in elementary school also find it difficult when they take the certification test. The aim of this activity is to provide training TOEIC tests to teachers. In the current era of globalization, it is not possible that standardized tests such as TOEIC be followed by teachers to support and improve their professionalsâ performance such as teacher certification. Therefore, it is necessary to the introduction of the TOEIC test for teachers who have adapted to their needs. This activity was held in SDN Pagelaran 04 Bogor, while the participants are all teachers at SDN Pagelaran 04 Bogor. . The method of implementing this activity is through two sessions, the first session is an explanation of TOEIC which the team previously pre-tested the TOEIC questions and then the two-team session gave post test questions. From the evaluation of the TOEIC Training To the SDN Teachers Pagelaran 04 Ciomas - Bogor In order to prepare for Teacher Certification, the participants do at the end of the activity it is seen that the teachers have started to understand and can do the TOEIC test although in terms of language skills it is necessary that the training intense to improve the quality of teaching and improve the quality of professional fieldsÂ Keywords : TOEIC, teacher, certification.Â AbstrakTOEIC atau Test Of English for International Communication adalah standar tes yang digunakan untuk mengukur kemampuan bahasa Inggris penutur non-bahasa Inggris dalam penggunaan bahasa Inggris sehari-hari di lingkungan kerja. Sertifikasi guru merupakan hal mutlak yang harus dilalui oleh seluruh guru-guru di Indonesia. Tidak jarang dari para guru tersebut mengalami kendala dalam mengerjakan soal-soal yagn diujikan dalam sertifikasi guru, Karena beberapa soal tersebut tersaji dalam bentuk Bahasa Inggris. Banyak hal yang dapat mendukung seorang guru lolos sertifikasi. Tidak hanya mengenai pemberkasan yang berhubungan dengan masa kerja guru tersebut disekolah, tetapi lulus tes tulis pun sangat berpengaruh dalam sertifikasi guru. Kadang para guru SD tidak lolos ujian tertulis dikarenakan mereka kurang paham dengan soal-soal Bahasa Inggris. Bahkan guru Bahasa Inggris di SD pun merasa kesulitan ketika mereka mengikuti tes sertifikasi. Tujuan yang ingin dicapai pada kegiatan ini adalah memberikan pelatihan tes TOEIC kepada guru-guru melalui pelatihan tes TOEIC. Dalam era globalisasi saat ini, tidak memungkinkan bahwa tes standar seperti TOEIC harus diikuti oleh guru-guru guna mendukung meningkatkan kinerja secara profesional seperti sertifikasi guru. Oleh karena itu diperlukan adanya pengenalan tes TOEIC untuk guru-guru yang yang telah disesuaikan dengan kebutuhan mereka. Kegiatan ini dilaksanakan di SDN Pagelaran 04 Bogor, adapun peserta kegiatan ini adalah seluruh guru SDN Pagelaran 04 Bogor. Metode pelaksanaan kegiatan ini melalui dua sesi, sesi pertama adalah penjelasan mengenai TOEIC yang mana sebelumnya tim melakukan pre-test soal-soal TOEIC dan kemudian sesi dua tim memberikan soal post test. Dari hasil evaluasi terhadap Pelatihan TOEIC Kepada Guru-Guru SDN Pagelaran 04 Ciomas â Bogor Dalam Rangka Persiapan menghadapi Sertifikasi Guru, yang peserta lakukan di akhir kegitan terlihat bahwa para guru sudah mulai paham dan bisa mengerjakan tes TOEICÂ walaupun dari segi ketrampilan berbahasa perlu adanya pelatihan yang intens untuk meningkatkan kualitas pengajaran maupun meningkatkan kualitas bidang profesi.Â Kata kunci : TOEIC, guru, sertifikasi